PERFORMANCE OF CORN COB ACTIVATED CARBON AS FILTER MEDIA IN RAINWATER TREATMENT - Abu Bakar, A. A.; Ahmad Fathani, S. U. (Journal of Engineering and Technology (JET), 2025)
This study investigates the utilisation of corn cob activated carbon filters in rainwater collection systems. A significant number of conventional water filters utilise non-recyclable materials, hence giving rise to environmental problems over their disposal. The research encompassed the development of a filter utilising corn cob as a natural waste material, the evaluation of water quality pre- and post-treatment, and the assessment of the filter’s efficacy. The activated carbon layer varied among the three designs: Design 1 had no activated carbon, Design 2 had 10 g, and Design 3 had 50 g. The experiments conducted assessed multiple water quality indicators, such as turbidity, colour, pH, nitrate, total dissolved solids, coliform, and E. coli. The examination of the gathered data indicated that Design 3 is the most efficacious course of treatment. The study conclusively demonstrated the effectiveness of corn cob activated carbon filters in substantially enhancing the quality of rainwater.